Formation of HCN+ in collisions of N+ and N2+ with a self-assembled propanethiol surface on gold. Issue 13 (5th October 2020) - Hechenberger, Faro; Kollotzek, Siegfried; Ballauf, Lorenz; Duensing, Felix; Ončák, Milan; Herman, Zdenek; Scheier, Paul
Abstract : Collisions of N + and N2 + with C3 hydrocarbons, represented by a self assembled monolayer of propanethiol on a polycrystalline gold surface, were investigated by experiments over the incident energy range between 5 eV and 100 eV. Abstract : Collisions of N + and N2 + with C3 hydrocarbons, represented by a self assembled monolayer of propanethiol on a polcrystalline gold surface, were investigated by experiments over the incident energy range between 5 eV and 100 eV. For N +, formation of HCN + is observed at incident energies of projectile ions as low as 20 eV. In the case of N2 + projectile ions, the yield of HCN + increased above zero only at incident energies of about 50 eV. This collision energy in the laboratory frame corresponds to an activation energy of about 3 eV to 3.5 eV. In the case of N + projectile ions, the yield of HCN + was large for most of the incident energy range, but decreased to zero at incident energies below 20 eV. This may indicate a very small energy threshold for the surface reaction between N + and C3 hydrocarbons of a few tenths of an eV. Such a threshold for the formation of HCN + may exist also for collisions of N + with an adsorbed mixture of hydrocarbon molecules.